Short Report – Birth Weight is Not Associated With Cataracts or Pseudophakia – Results from the Gutenberg Health Study - Fieß A; Gißler S; Grabitz S; Wild PS; Lackner KJ; Beutel ME; Urschitz MS; Tüscher O; Münzel T; Schattenberg JM; Konstantinides SV; Pfeiffer N; et al. (Clinical Ophthalmology)
Achim Fieß,1,* Sandra Gißler,1,* Stephanie Grabitz,1 Philipp S Wild,2– 5 Karl J Lackner,6 Manfred E Beutel,7 Michael S Urschitz,8 Oliver Tüscher,5,9,10 Thomas Münzel,11 Jörn M Schattenberg,12,13 Stavros V Konstantinides,2,14 Norbert Pfeiffer,1 Alexander K Schuster1 1Department of Ophthalmology, University Medical Center of the Johannes Gutenberg University Mainz, Mainz, Germany; 2Center for Thrombosis and Hemostasis, University Medical Center Mainz, Mainz, Germany; 3German Center for Cardiovascular Research (DZHK), Partner Site Rhine-Main, Mainz, Germany; 4Preventive Cardiology and Preventive Medicine-Department of Cardiology, University Medical Center Mainz, Mainz, Germany; 5Institute of Molecular Biology (IMB), Mainz, Germany; 6Institute of Clinical Chemistry and Laboratory Medicine, University Medical Center of the Johannes Gutenberg-University Mainz, Mainz, Germany; 7Department of Psychosomatic Medicine and Psychotherapy, University Medical Center of the Johannes Gutenberg University Mainz, Mainz, Germany; 8Division of Pediatric Epidemiology, Institute for Medical Biostatistics, Epidemiology and Informatics, University Medical Center of the Johannes Gutenberg University Mainz, Mainz, Germany; 9Clinic for Psychiatry and Psychotherapy, University Medical Center of the Johannes Gutenberg-University Mainz, Mainz, Germany; 10Leibniz Institute for Resilience Research, Mainz, Germany; 11Center for Cardiology-Cardiology I, University Medical Center of the Johannes Gutenberg-University Mainz, Mainz, Germany; 12Department of Internal Medicine II, Saarland University Medical Center, Homburg, Germany; 13Department of Internal Medicine I, University Medical Center, Mainz, Germany; 14Department of Cardiology, Democritus University of Thrace, Alexandroupolis, 68100, Greece*These authors contributed equally to this workCorrespondence: Achim Fieß, Department of Ophthalmology, Medical Center of the Johannes Gutenberg University Mainz, Langenbeckstr 1, Mainz, 55131, Germany, Tel +49-(0)6131-17-5150, Fax +49-(0)6131-17-8495, Email achim.fiess@gmail.comAbstract: This study investigates the association between self-reported birth weight (BW) and the frequency of cataract and pseudophakia in a large population-based cohort in Germany, as part of the Gutenberg Health Study (GHS). Slit lamp examination and Scheimpflug imaging of 8205 participants, aged 35 to 74, were assessed and signs of cataract or pseudophakia analyzed. The research aimed to explore the correlation between fetal growth restriction and/or prematurity indicated by BW and the frequency of cataract and pseudophakia. In the univariable analysis, cataract was initially associated with low and high BW, but this association disappeared after adjusting for age, sex, examiner and cardiovascular risk factors. No association was found between low BW and pseudophakia or the frequency of cataract surgery within 5 years. The study reveals novel insights from a large population-based study specifically exploring this association.Keywords: Cataract, pseudophakia, birth weight, epidemiology, population-based study